Preferences for REDD+ Contract Attributes in Low-Income Countries : A Choice Experiment in Ethiopia - Dissanayake, Sahan T. M. (World Bank, Washington, DC, 2015)
This paper informs the national and international policy discussions related to the adoption of the United Nations Reducing Emissions from Deforestation and Forest Degradation Programme. Effective program instruments must carefully consider incentives, opportunity costs, and community interactions. A choice experiment survey was applied to rural Ethiopian communities to understand respondents’ preferences toward the institutional structure of the program contracts. The results show that respondents have particular preferences about how Reducing Emissions from Deforestation and Forest Degradation programs are structured with regard to the manner in which the payments are divided between the households and the communities, the restrictions on using grazing land, and the level of payments received for the program. Surprisingly, restrictions on firewood collection do not significantly impact contract choice. The paper further analyzes the structure of the preferences by using attribute interaction terms and socio-demographic interaction terms. The analysis finds significant regional variation in preferences, indicating that Reducing Emissions from Deforestation and Forest Degradation should be tailored to specific regions. Finally, the marginal willingness to pay for attributes is calculated using the traditional preference space approach, as well as the more recent willingness-to-pay approach.